The Palgrave Handbook of Media and Communication Research in Africa (Springer International Publishing, 2018)
This handbook attempts to fill the gap in empirical scholarship of media and communication research in Africa, from an Africanist perspective. The collection draws on expert knowledge of key media and communication scholars in Africa and the diaspora, offering a counter-narrative to existing Western and Eurocentric discourses of knowledge-production. As the decolonial turn takes centre stage across Africa, this collection further rethinks media and communication research in a post-colonial setting and provides empirical evidence as to why some of the methods conceptualised in Europe will not work in Africa. The result is a thorough appraisal of the current threats, challenges and opportunities facing the discipline on the continent.